2012
DOI: 10.1103/physrevb.85.115443
|View full text |Cite
|
Sign up to set email alerts
|

Creation of particle-hole superposition states in graphene at multiphoton resonant excitation by laser radiation

Abstract: Nonlinear dynamics of establishment of electron-hole coherent superpositions states in graphene by multiphoton resonant excitation of interband transitions in laser fields is considered. The singleparticle time dependent density matrix for such a quantized system is calculated in the multiphoton resonant approximation. The dependence of Rabi oscillations of Fermi-Dirac sea in graphene on the time, momentum, and photon number at multiphoton laser-excitation is analyzed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 41 publications
0
72
0
Order By: Relevance
“…Recent theoretical investigations of nonlinear optical effects arising from interband electronic transitions have revealed that, despite graphene's single-atomic-layer thickness, its nonlinear optical response is particularly strong [19][20][21]. The potential of graphene as a functional nonlinear optical material has engendered many nonlinear optical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical investigations of nonlinear optical effects arising from interband electronic transitions have revealed that, despite graphene's single-atomic-layer thickness, its nonlinear optical response is particularly strong [19][20][21]. The potential of graphene as a functional nonlinear optical material has engendered many nonlinear optical studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dependence of the nonlinearity on chemical potential, temperature, and the excitation frequency have not been systematically measured. Of the theoretical studies reported, most are still at the level of single particle approximations within different approaches, which include perturbative treatments based on Fermi's golden rule [25,26], the quasiclassical Boltzmann kinetic approach [1,2,27,28], and quantum treatments based on semiconductor Bloch equations (SBE) or equivalent strategies [3,[29][30][31][32][33][34][35][36][37][38]. When optical transitions around the Dirac points dominate, analytic expressions for the third order conductivities can be obtained perturbatively by employing the linear dispersion approximation [3,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Having the purpose of presenting and describing specific results for the multiphoton transitions, our consideration is limited to the Josephson-junction qubits. We note however that similar phenomena can be studied in different quantum objects, which can be described as two-or multi-level systems, such as quantum wires and dots [56][57][58][59][60], nitrogen vacancy centers in diamond [61,62], ultracold atoms [63][64][65], nanomechanical and optomechanical setups [66][67][68], electronic spin systems, two-dimensional electron gas, and graphene [69][70][71].…”
Section: Introductionmentioning
confidence: 99%